European multicentre experience of staged hybrid atrial fibrillation ablation for the treatment of persistent and longstanding persistent atrial fibrillation - Haywood, G A; Varini, R; Osmancik, P; Cireddu, M; Caldwell, J; Chaudhry, M A; Loubani, M; Della Bella, P; Lapenna, E; Budera, P; Dalrymple-Hay, M (International journal of cardiology. Heart & vasculature, 2020)
UNLABELLED: The management of non-paroxysmal atrial fibrillation (AF) remains controversial. We examined the efficacy and safety of the 2 stage Hybrid AF ablation approach by analysing the largest series of this technique reported so far. METHODS: The approach aims to electrically isolate the left atrial posterior wall incorporating the pulmonary veins ('box-set'pattern). An initial video-assisted thoracoscopic (VATS) epicardial ablation is followed after a minimum of 8 weeks by endocardial radiofrequency catheter ablation. RESULTS: Of 175 patients from 4 European cardiothoracic centers, who underwent the surgical (COBRA Fusion, AtriCure Inc) 1st stage ablation, 166 went on to complete 2nd stage catheter ablation. At median follow up of 18 months post 2nd stage procedure 93/166 (56%) had remained free of AF or atrial tachycardia (AT) recurrence off antiarrhythmic drugs. 110/175 62.9% were in sinus rhythm off all antiarrhythmic drugs at last clinic follow-up (132/175 75.4% including those on antiarrhythmic drugs). 18 patients (10.8%) underwent a further re-do ablation (mean of 1.1 ablations per patient) 105/166 (63%) remained free of AF/AT recurrence off antiarrhythmic drugs following last ablation procedure.Latterly, ILRs have been implanted in patients (n = 56); 60% have remained fully arrhythmia free and 80% have shown AF burden < 5% at a median 14 months follow-up [IQR: 13.5 (8-21.5)]. Only 10.9% have reverted to persistent AF. 5 patients (2.9%) had a perioperative stroke and 4 patients (2.3%) exhibited persistent weakness of the right hemidiaphragm following stage 1 VATS epicardial ablation. One patient died following stroke (overall mortality 0.6%). CONCLUSIONS: In patients with non-paroxysmal AF with unfavourable characteristics for catheter ablation, the staged hybrid approach results in acceptable levels of freedom from recurrent atrial arrhythmia, however, complication rates are higher than with catheter ablation alone.
Keywords: Left atrial posterior wall isolation; Persistent atrial fibrillation; Longstanding persistent atrial fibrillation; Catheter ablation; Hybrid ablation